Production of bovine embryos in vitro through in vitro fertilisation (ivf) and intracytoplasmic sperm injection (icsi) techniques / Nor Fadillah Binti Awang - Awang, Nor Fadillah (2013)
The objective of this study was to develop an optimal in vitro produced embryos (IVP) protocol using two methods of insemination, namely in vitro fertilisation (IVF) and intracytoplasmic sperm injection (ICSI) protocols by using different qualities of oocytes in Malaysian cattle. The ovaries were collected from slaughtered cattle from the local abattoir. The oocyte morphology was observed and grouped into three groups: Groups A, B and C, based on cumulus cell compactness. Then the oocytes were subdivided based on the cytoplasm quality, namely homogenous and heterogenous (Experiment 1). The oocytes were matured in humidified 5% CO2 incubator at 38.5°C at different maturation durations of 20, 24 and 28 hours (Experiment 2). The matured oocytes were fertilised with frozen-thawed sperm before being cultured. The cleavage rate and embryo development were evaluated. The serum was added at every embryo development stage to develop up to blastocyst stage (Experiment 3). In ICSI study, the different oocytes and sperm groups were used (Experiments 4 and 5) to produce ICSI embryos. Finally, comparison was made between IVF- and ICSI-derived embryos (Experiment 6). The oocyte quality (the presence of cumulus cells and different cytoplasmic group), IVM duration and culture medium supplement were considered among the important factors affecting the maturation, fertilisation and culture competence of bovine embryos during IVMFC procedures to produce IVF-derived embryos. In Experiment 1, the percentage of matured-fertilised oocytes differed between the three groups of oocytes. Homogenous cytoplasm, Grade A oocytes gave the highest 2-cell cleavage rate (78.30%) followed by Grade B (65.92%) and Grade C (24.02%) iii compared to heterogenous cytoplasm with 50.90%, 30.48% and 11.66%, respectively. It was consistently shown that homogenous cytoplasm gave higher cleavage rates for all the grades of oocyte. It was also observed that blastocysts were obtained for Grade A – Homogenous (28.55%), Grade A – Heterogenous (2.66%) and Grade B – Homogenous (14.40%) oocytes. In Experiment 2, 24 hours IVM duration gave better results (P<0.05) compared to 20- and 28-hours for homogenous cytoplasm. But, there were no significant differences when compared to Group B – Homogenous at same IVM duration. For cleavage rate for 20 hours maturation duration, Grade A - Homogenous gave the highest 2-cell cleavage rate (58.57%), followed by Grade B (38.32%) and Grade C (15.58%). For heterogenous cytoplasm, development values were 45.65%, 39.64% and 21.66%, respectively. It was also observed that higher percent blastocyst was obtained for 24 hours IVM duration from Grade A – Homogenous (28.55%) than Grade B - Homogenous (14.40%) compared to 20 and 28 hours IVM duration. In Experiment 3, the blastocyst development after serum addition at morula stage was 63.06%, including fully expanded and hatch blastocyst formation (47.58 % and 26.34%, respectively). It showed that serum could be beneficial to be added at morula stage, conversely, addition of serum at earlier stages of development might be detrimental to embryonic development as no blastocyst was developed after serum addition at 2-cell and 4-cell stages. ICSI-derived embryos production in Experiment 4 showed that Grade A COC gave the highest 2-cell cleavage rate (44.53%) followed by Grade B (38.94%) and Grade C (7.85%). It was also observed that morula stage was only obtained in Grade A (16.65%). The cleavage rates obtained from different sperm quality injected into oocytes during ICSI (Experiment 5) showed that the cleavage rates (at 2-cell stage) of iv intact-immobilised was the highest (63.42%) compared to other sperm quality. Comparison study of IVF- and ICSI-derived embryos (Experiment 6) showed that IVF embryos gave higher cleavage rate in all cases of embryonic development than the ICSI embryo with values of 66.77% versus 41.74% for 2-cell and 8.94% versus 0.00% for blastocyst stage, respectively. In conclusions, the results of the present study showed that the quality of oocytes, sperm, IVM duration and culture supplement influenced the maturation, fertilisation and culture of IVF- and ICSI-derived embryos. The morphology of cumulus cells and oocytes cytoplasm influenced the maturation, fertilisation and developmental competence of both IVP embryos. Group A COC gave better results followed by Groups B and C with homogenous cytoplasm was superior then heterogenous cytoplasm. 24-hour IVM duration gave the best maturational rate compared with other IVM duration. The use of immobilised intact sperm produced better results than other groups of sperm during ICSI procedure. Serum addition in culture medium did help in blastocyst formation if added at later stage of embryo development but could be detrimental to early stage embryos.